Psicomotricidad y su influencia en la metodología del aprendizaje en los niños de la Unidad Educativa San José de la ciudad de Babahoyo - Rivadeneira Vera, Dayana Sasha (2019)
In the early age or initial stage as it is also known at the age where children begin to develop their basic motor skills, sometimes it goes unnoticed and they do not receive any stimulation as it should to reach their maximum expression, it is in this at which time the problems and psychomotor limitations that students may have in the first school levels begin to set, where it is common to observe students who have difficulty performing movement and activities that involve small muscles or also the coordination of their body parts In gross motor skills, from this point of view the present research work developed its objective in analyzing the influence that psychomotor skills have on the learning methodology of the initial students. For the development of this research work, the non-experimental design, of cross-sectional use with the qualitative and quantitative modality, of descriptive, explanatory and exploratory type, documentary, field, inductive and deductive methods with a population consisting of parents and teachers was used of initial and to the director of the institution, to whom surveys and interviews were applied, obtaining as results that exercises are not carried out for the psychomotor either viso-motor or oculic-medical coordination during the classes, which limits the application of the methodology of learning in children of the initial level, and must present this alternative theoretical proposal didactic guide of application of motor exercises to develop psychomotor skills in children of initial level